The moderating effects of psychological empowerment on junior lecturers’ technology commercialisation intention - Lee, Van (2023)
Nowadays, Malaysia faced the landscape of university technology commercialisation still in development phase, which should put huge of efforts and attentions. Even though the importance of university technology commercialisation was acknowledged, the comprehension on factors that influencing technology commercialisation intention particularly of junior lecturers group remained limited. Hence, this study aimed at identifying the influential determinants of junior lecturers’ technology commercialisation intention and determining moderating effects of psychological empowerment toward relationships among them. On the basic of literature review, Theory of Planned Behaviour (TPB) and psychological empowerment theory were adopted as theoretical foundations of this study. The data of this quantitative research were collected by mail survey questionnaire, which based on purposive sampling and minimum of 102 responses. As the data analysis using the Statistical Packages for the Social Sciences (SPSS) was conducted with prior, then proceeded to Partial Least Squares Structural Equation Modelling (PLS-SEM). The research findings revealed the positive effects of personal attitude and perceived behavioural control on technology commercialisation intention, except for subjective norm. Nevertheless, psychological empowerment was had significant moderating effect on relationship between subjective norm and technology commercialisation intention, but did not show on the other two relationships. In consequence, these research findings were important to clarify technology commercialisation intentions of junior lecturers, thereby could boost continuous improvements for technology transfer in public universities